2008
DOI: 10.1063/1.2823053
|View full text |Cite
|
Sign up to set email alerts
|

On the performance of two-component energy-consistent pseudopotentials in atomic Fock-space coupled cluster calculations

Abstract: The four-component atomic intermediate-Hamiltonian Fock-space coupled cluster (IHFSCC) code of Landau et al. [J. Chem. Phys. 115, 6862 (2001)] has been adapted to two-component calculations with relativistic pseudopotentials of the energy-consistent variety. Recently adjusted energy-consistent pseudopotentials for group 11 and 12 transition elements as well as group 13 and 14 post-d main group elements, which were fitted to atomic valence spectra from four-component multiconfiguration Dirac-Hartree-Fock calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…The present value for electron affinity is in good agreement with a substantial number of previous theoretical calculations (7) 170.6(6) Williams et al [15] LPES 404(9) 76(9) 175(9) Theory Guo et al [16] LSD-GX 371 Arnau et al [17] CIPSI 380 Wijesundera [18] MCDF 393 Eliav et al [19] RCC 419 Sundholm et al [20] MCHF-CCSD 374(15) Figgen et al [21] IHFSCC 403 (see Table II). The theoretical results of Arnau et al [17], Wijesundera [18], and Sundholm et al [20] are particularly close to the present value, each being within 10 meV.…”
Section: Thresholdsupporting
confidence: 87%
See 2 more Smart Citations
“…The present value for electron affinity is in good agreement with a substantial number of previous theoretical calculations (7) 170.6(6) Williams et al [15] LPES 404(9) 76(9) 175(9) Theory Guo et al [16] LSD-GX 371 Arnau et al [17] CIPSI 380 Wijesundera [18] MCDF 393 Eliav et al [19] RCC 419 Sundholm et al [20] MCHF-CCSD 374(15) Figgen et al [21] IHFSCC 403 (see Table II). The theoretical results of Arnau et al [17], Wijesundera [18], and Sundholm et al [20] are particularly close to the present value, each being within 10 meV.…”
Section: Thresholdsupporting
confidence: 87%
“…Our result for the electron affinity of 383.92(6) meV substantially revises the previous measurement of 404 (9) meV [15]. The uncertainty of the previous experimental value (9 meV) [15] is of the same order of magnitude as the spread of the existing theoretical values, which range from 371 to 419 meV [16][17][18][19][20][21]. Our present measurement of the electron affinity yields an uncertainty (0.06 meV) that is two orders of magnitude smaller than the uncertainty of the earlier measurement, thus providing an excellent test case for state-of-the-art atomic structure theory that incorporates detailed analysis of correlation for both the valence and core electrons.…”
Section: Thresholdsupporting
confidence: 73%
See 1 more Smart Citation
“…Both experiments indicate that the excited levels are either unbound or too weakly bound to be detected, although the three fine-structure levels 3 P 0,1,2 were detected as bound states for the lighter elements of the same Group 13 (B − , Al − , Ga − and In − ) [12][13][14][15][16][17]. Number of theoretical studies on the EA of Tl have been reported using a variety of computational methods [18][19][20][21][22][23][24][25], but their results show poor agreement. For example, using different theoretical methods, Arnau et al [18] and Felfli et al [24] predicted the EA of Tl to be 270 meV and 2415 meV, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Since then the development and applications of the energy-consistent relativistic ECP thrived. [49][50][51][52][53] In addition to the SOC, the generalized relativistic ECP ͑Refs. 54 and 55͒ even attempted to include the Breit interaction in calculations for actinides.…”
Section: Introductionmentioning
confidence: 99%